A prospective and randomized clinical trial evaluating the effectiveness of ART restorations with high-viscosity glass-ionomer cement versus conventional restorations with resin composite in Class II cavities of permanent teeth: two-year follow-up - Rafael MENEZES-SILVA; Sofia R Maito VELASCO; Eduardo BRESCIANi; Roosevelt da Silva BASTOS; Maria Fidela de Lima NAVARRO (University of São Paulo, 2021)
Abstract Objective To compare the effectiveness of ART restorations using High Viscosity Glass-ionomer cement (HVGIC) with conventional restorations using resin composite in Class II cavities of permanent teeth, in a 2-year follow-up. Methodology Seventy-seven restorations were made with each restorative material, Equia Fil-GC Corporation (ART restorations) and Z350-3M (conventional restoration), in 54 participants in this parallel and randomized clinical trial. Restorations were evaluated at 6 months, 1 and 2 years using the ART and the modified United States Public Health Service (USPHS) criteria. Chi-square test and Survival Analysis (p<0.05) were used for statistical analysis. Results The success rates for ART restorations were 98.7% (6 months) and 95.8% (1 year) for both criteria. At 2 years, success rate was 92% and 90.3% when scored by the modified USPHS and ART criteria (p=0.466), respectively. The success rates for conventional restorations were 100% (6 months), 98.7% (1 year) and 91.5% (2 years) for both assessment criteria. ART restorations presented a lower survival rate by the criterion of ART (83.7%) when compared to the modified USPHS criterion of (87.8%), after 2 years (p=0.051). The survival of conventional restorations was 90.7% for both evaluation criteria. Conclusion At the 2-years follow-up evaluation, no statistically significant difference was observed between the success rate of ART restorations with HVGIC compared to conventional restorations with resin composite in Class II cavities of permanent teeth.